BUDIDAYA AZOLLA SEBAGAI ALTERNATIF PAKAN IKAN ALAMI DI KELURAHAN KEMPAS JAYA - Heltina, Desi; Liyana , Audi; Laia , Ferlinus Saputra; Ramadhani , Micha Vania; Primbodo , Selo Bambang; Yahlim , Wasiah Fichtimar (Inspirasi: Jurnal Pengabdian Masyarakat, 2024)
Cultivating Azolla as an alternative natural feed in Kempas Jaya Subdistrict aims to enable fish farmers to know how to cultivate Azolla, use Azolla as an alternative natural feed for fish and can increase the income of fish farming entrepreneurs by reducing the cost of fish feed. The main issues identified include dependence on expensive commercial animal feed. The aim of this service is to introduce Azolla as a natural feed solution that is efficient, economical and sustainable. The method is carried out by socializing Azolla cultivation including the benefits objectives of Azolla cultivation, Azolla microphylla cultivation techniques in tarpaulin ponds as well as challenges and obstacles in Azolla cultivation. The result of the service is that many activity participants finally know the benefits and objectives of Azolla cultivation, know the techniques for cultivating Azolla microphylla in tarpaulin ponds as well as the challenges and obstacles in cultivating Azolla as an alternative fish feed. This success also has a positive impact on local economic and environmental prosperity.